Strategi Pembelajaran Giving Question and Getting Answer (GQGA) dalam Keterampilan Berbicara - Nur Arifah; Mantasiah R; Nurming Saleh (Phonologie : Journal of Language and Literature, 2023)
Abstract. The aim of this research was to get the data on the effectiveness of using the learning strategies Giving Question and Getting Answer of the speaking ability of the students of class X at SMA Negeri 11 Enrekang. This research is Quasy Experiment Design Model Noneequivalent Control Group Design. The population of this study was Class X SMA Negeri 11 Enrekang students, which consisted of 82 students. Were class X.1 as experimental class consist of 18 students and X.3 as control class consist of 18 students and are selected from random sampling. The data analysis in this research uses a t-test. The result shows that tcount=05 < ttable=032 with a significance level of 0.05. This means that learning strategies Giving Question and Getting Answer is not effective in the speaking ability of the X grade students at SMA Negeri 11 Enrekang.Keyword: Effectiveness, Learning Strategies, Giving Questions and Getting Answers, Speaking Skills